Can communication effectiveness promote patients’ revisit intentions through trust and perceived value? A study of private hospitals in Yangon: 10.55131/jphd/2025/230317 - Ratasuk, Akaraphun; Nyan Lin Naing (Journal of Public Health and Development, 2025)
Due to the competitive Myanmar healthcare industry, this study investigated the impact of communication effectiveness on promoting patients’ revisit intentions through the roles of patients’ trust and perceived value as a mediator, framed by social capital theory, in private hospitals in Yangon, the previous capital city and one of the largest cities of the country. Given the unknown population of patients in Yangon, survey data were gathered using online questionnaires designed in Burmese through local private healthcare online communities for one month from 414 private hospital patients across 15 townships of Yangon, Myanmar, selected using stratified purposive sampling, representing a response ratio of 69%. The reliability of the data was confirmed, with all constructs achieving Cronbach’s alpha values above 0.872, indicating strong internal consistency. According to the PLS-SEM analysis and the Sobel test results, communication effectiveness directly influenced revisit intentions (β= 0.0152, p< 0.014). Moreover, trust (t=2.104, p=0.000) and perceived value (t= 2.552, p= 0.000) indirectly mediated the relationship between communication effectiveness and revisit intentions as well as the perceived value mediated the relationship between the patient trust and revisit intentions (t= 8.836, p= 0.000). These findings contribute new knowledge and insights into the roles of communication effectiveness in promoting revisit intentions through trust and perceived value of patients in private hospitals in Yangon, Myanmar, and new expansion of social capital theory in healthcare literature, which has not yet been widely explored. Furthermore, the study provides valuable guidelines for healthcare service providers, policymakers, and marketers in promoting healthcare businesses’ long-term success.